The effects of concurrent aerobic and strength training on muscle fiber hypertrophy: a systematic review and meta-analysis - Lundberg, T. R.; Feuerbacher, J. F.; Sünkeler, M.; Schumann, M. (Sports Medicine, 2022)
Background: Whole muscle hypertrophy does not appear to be negatively affected by concurrent aerobic and strength training compared to strength training alone. However, there are contradictions in the literature regarding the effects of concurrent training on hypertrophy at the myofiber level. Objective: The current study aimed to systematically examine the extent to which concurrent aerobic and strength training, compared with strength training alone, influences type I and type II muscle fiber size adaptations. We also conducted subgroup analyses to examine the effects of the type of aerobic training, training modality, exercise order, training frequency, age, and training status. Design: A systematic literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [PROSPERO: CRD42020203777]. The registered protocol was modified to include only muscle fiber hypertrophy as an outcome. Data Sources: PubMed/MEDLINE, ISI Web of Science, Embase, CINAHL, SPORTDiscus, and Scopus were systematically searched on 12 August, 2020, and updated on 15 March, 2021. Eligibility Criteria: Population: healthy adults of any sex and age; intervention: supervised, concurrent aerobic and strength training of at least 4 weeks; comparison: identical strength training prescription, with no aerobic training; and outcome: muscle fiber hypertrophy. Results: A total of 15 studies were included. The estimated standardized mean difference based on the random-effects model was - 0.23 (95% confidence interval [CI] - 0.46 to - 0.00, p = 0.050) for overall muscle fiber hypertrophy. The standardized mean differences were - 0.34 (95% CI - 0.72 to 0.04, p = 0.078) and - 0.13 (95% CI - 0.39 to 0.12, p = 0.315) for type I and type II fiber hypertrophy, respectively. A negative effect of concurrent training was observed for type I fibers when aerobic training was performed by running but not cycling (standardized mean difference - 0.81, 95% CI - 1.26 to - 0.36). None of the other subgroup analyses (i.e., based on concurrent training frequency, training status, training modality, and training order of same-session training) revealed any differences between groups. Conclusions: In contrast to previous findings on whole muscle hypertrophy, the present results suggest that concurrent aerobic and strength training may have a small negative effect on fiber hypertrophy compared with strength training alone. Preliminary evidence suggests that this interference effect may be more pronounced when aerobic training is performed by running compared with cycling, at least for type I fibers.